Principle Assignments for the First Time and Over Again: An Assessment on Oral Exam - Kemal Kayıkçı; İzzet Özdemir; Gülnar Özyıldırım (Educational Administration: Theory and Practice, 2021)
The regulation, regarding to assignment of administrators of educational institutions which are depended on Ministry of National Education, came into force on 10/06/2014. The aim of this study is to determine the view of school administrator candidates on the first time and re-assignment of school administrators’ process which was applied with the regulation in question. This study is a qualitative research and a case study as the design method. Maximum variation sampling method which is a type of purposive sampling techniques was used for the determination of the samples. The study group consists of 12 participants, working in Antalya Province. In the research, individual interview technique was used. Data were collected through semi-structured interview form and examined by being used content analysis technique. Although participants found the topics of the oral exam evaluation appropriate, they thought that the duration of the oral test was short and the oral exam issues could not be measured with three short-answer questions. Moreover; they were in opinion that there wasn’t an objective evaluation and it was not accurate to selection of school administrators with oral test. Also, they suggested that they should be an assistant administrator before being a school administrator; they should take pre-service management training; there should be done a written exam and an evaluation that spreads to process as well as being a school administrator should be associated with other administrations.